Komparasi Artikel Ilmiah Tentang Pengembangan Koleksi Perpustakaan: Comparison of Scientific Articles on The Development of Library Collections - Arin Luthfiyah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
This research is entitled "scientific article collaboration on library collection development". The purpose of this research is to find out how the collection development process is carried out in the library in particular. This study uses a qualitative research design. By collecting primary data, secondary and literature review. Data analysis techniques using data presentation, drawing conclusions. The results of this study. This shows that collection development is an important and vital activity in the library. There is no library without collections, both print, non-print and electronic collections to meet their various information needs. Library collection development is very important for library growth, therefore it needs to be continuously evaluated to assess their strengths and weaknesses. This process will lead to the removal of material that is no longer relevant. Given the shortage of books in libraries and based on the premise that no library is independent, libraries engage in inter-library lending or sharing of resources. Information Communication Technology based on on-line access related to collection development in developed countries.